Review: Chronic endometritis and its effect on reproduction. Issue 5 (6th March 2019) - Kimura, Fuminori; Takebayashi, Akie; Ishida, Mitsuaki; Nakamura, Akiko; Kitazawa, Jun; Morimune, Aina; Hirata, Kimiko; Takahashi, Akimasa; Tsuji, Shoko; Takashima, Akiko; Amano, Tsukuru; Tsuji, Shunichiro; et al.
Abstract: Aim: Chronic endometritis (CE) is a disease of continuous and subtle inflammation characterized by the infiltration of plasma cells in the endometrial stromal area. Although the clinical significance of CE has been thought in clinical practice for a long time because it is either asymptomatic or presents with subtle symptoms, recent studies have shown the potential adverse effects of CE on fertility. In the present review, we focus on the concept, diagnosis, etiology, pathophysiology, diagnosis, impact on reproduction and treatment for it to understand CE. Methods: The published articles were reviewed. Results: The prevalence of CE has been found to be 2.8–56.8% in infertile women, 14–67.5% in women with recurrent implantation failure (RIF), and 9.3–67.6% in women with recurrent pregnancy loss. Microorganisms are thought to be a main cause of CE, since antibiotic treatment has been reported to be an effective therapy for CE. Common bacteria are frequently detected in the uterine cavity of CE patients by microbial culture. In CE endometrium, the prevalence of immune cells and decidualization has been reported to be modified, and these modifications are thought to adversely affect fertility. The gold standard for the diagnosis of CE is the histological detection of plasma cells in the stromal area of the endometrium in endometrial specimens, although universally accepted criteria for the diagnosis of CE have not been determined. The treatment currently thought to be most effective for the recovery of fertility in CE is administration of oral antibiotics. Patients whose CE has been cured have been reported to have a higher ongoing pregnancy rate, clinical pregnancy rate, and implantation rate compared with patients with persistent CE. Conclusion: CE greatly affects implantation and impairs fertility. Antibiotic administration is an effective therapeutic option. Pregnancy rate in in vitro fertilization is improved when CE is cured by antibiotic.